2009
DOI: 10.1063/1.3238305
|View full text |Cite
|
Sign up to set email alerts
|

Atomic hydrogen interactions with amorphous carbon thin films

Abstract: The atomic-scale interactions of H atoms with hydrogenated amorphous carbon ͑a-C:H͒ films were identified using molecular dynamics ͑MD͒ simulations and experiments based on surface characterization tools. Realistic a-C:H films developed using MD simulations were impinged with H atoms with a kinetic energy corresponding to a temperature of 700 K. The specific chemical reactions of the H atoms with the a-C:H surface were identified through a detailed analysis of the MD trajectories. The MD simulations showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 71 publications
(96 reference statements)
3
41
0
Order By: Relevance
“…Regardless thereof, the reported surface roughness after deposition (or post-deposition treatment) is on the order of nanometers. 37,91,93,96 A surface roughness of a few nanometers is of the same order as the roughness found in this work during Ar/H 2 (or Ar/D 2 ) plasma etching. The roughness in a pure H 2 plasma on the other hand increased strongly as established in Sec.…”
Section: B Surface Roughnesssupporting
confidence: 80%
See 1 more Smart Citation
“…Regardless thereof, the reported surface roughness after deposition (or post-deposition treatment) is on the order of nanometers. 37,91,93,96 A surface roughness of a few nanometers is of the same order as the roughness found in this work during Ar/H 2 (or Ar/D 2 ) plasma etching. The roughness in a pure H 2 plasma on the other hand increased strongly as established in Sec.…”
Section: B Surface Roughnesssupporting
confidence: 80%
“…33,34 Chemical erosion can occur when an a-C:H sample is exposed to an atomic hydrogen beam. [35][36][37] An important step in chemical erosion is the conversion of sp 2 into sp 3 groups through hydrogenation. This will lead in some situations to the formation of a dangling bond (DB).…”
Section: Amorphous Carbon Etch Mechanismsmentioning
confidence: 99%
“…Physical sputtering techniques are mainly employed to deposit hydrogen free films where as chemical vapor deposition (CVD) based techniques result in hydrogenated films [5]. Moreover, hydrogen during film growth process creates dangling bonds and allows the adsorption of CH x species to the unsaturated carbon atoms which enhances sp 3 C-C bonding network in the film [6]. Presence of hydrogen in the films is also an advantageous factor because it determines the cross linking across sp 3 C-C bonding fraction.…”
Section: Introductionmentioning
confidence: 99%
“…This recombination, producing transient heating to temperatures in excess of 1000 K, has been well documented in laboratory experiments Yamaguchi & Wakabayashi 2004) and is quite likely to occur in structures such as that shown in Figure 11. In this case, the energy source would involve the recombination of stored H atoms (Sugai et al 1989), but radical recombination is also possible given the heterogeneous composition of these carbonaceous nanoparticles (Biener 1994;Jariwala et al 2009). Laboratory experiments have demonstrated that thermal energy released from an amorphous carbon layer on a core-mantle grain can produce significant heating (Kaito et al 2007).…”
Section: Comparison With Observationmentioning
confidence: 99%